MicroRNAs expression influence in ulcerative colitis and Crohn's disease: A pilot study for the identification of diagnostic biomarkers - Quaglio, Ana Elisa Valencise [UNESP]; Santaella, Felipe Jose [UNESP]; Rodrigues, Maria Aparecida Marchesan [UNESP]; Sassaki, Ligia Yukie [UNESP]; Di Stasi, Luiz Claudio [UNESP] (Baishideng Publishing Group, 2021)
from the Pathology Department of Botucatu Medical School at São Paulo State University (Unesp). The diagnosis of UC or CD was based on clinical, endoscopic, radiologic, and histological criteria and confirmed by histopathological analysis at the time of selection. The TaqMan™ Array Human MicroRNA A+B Cards Set v3.0 (Applied Biosystems™) platform was used to analyze 754 miRNAs. Targets of DE-miRNAs were predicted using miRNA Data Integration Portal (mirDIP) and the miRNA Target Interaction database (MiRTarBase). All statistical analyses were conducted using GraphPad Prism software. Parametric and nonparametric data were analyzed using t-tests and Mann-Whitney U tests, respectively. RESULTS The results showed that of the 754 miRNAs that were initially evaluated, 643 miRNAs were found to be expressed in at least five of the patients who were diagnosed with either CD or UC; the remaining 111 miRNAs were not considered to be expressed in these patients. The expression levels of 28 miRNAs were significantly different between the CD and UC patients (P ≤ 0.05); 13 miRNAs demonstrated a fold-change in expression level greater than 1. Five miRNAs with a downregulated expression were selected for enrichment analysis. The miRNAs whose expression levels were significantly lower in UC patients than in CD patients were enriched in certain signaling pathways that were mostly correlated with cancer-related processes and respective biomarkers. CONCLUSION MiRNAs could be used to differentiate UC from CD, and differently expressed miRNAs could help explain the distinct pathophysiology of each disease. BACKGROUND Inflammatory bowel disease (IBD) comprises two distinct diseases, Crohn’s disease (CD) and ulcerative colitis (UC), both of which are chronic, relapsing inflammatory disorders of the gastrointestinal tract with a mostly unknown etiology. The incidence and prevalence of IBD are continually increasing, indicating the need for further studies to investigate the genetic determinants of these diseases. Since microRNAs (miRNAs) regulate protein translation via complementary binding to mRNA, discovering differentially expressed miRNAs (DE) in UC or CD patients could be important for diagnostic biomarker identification, assisting in the appropriate disease differentiation progressing the understanding of IBD pathogenesis. AIM To determine the miRNA expression profile in UC and CD patients and the potential pathophysiological contributions of differentially expressed miRNA. METHODS A total of 20 formalin-fixed paraffin-embedded colonic samples were collected
Keywords: Biomarker; Crohn’s disease; Differential diagnosis; Inflammatory bowel disease; MiRNA; Ulcerative colitis